2015
DOI: 10.1097/nhh.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Professional Boundary Violations

Abstract: The purpose of this article is to review the nursing literature related to professional boundary violations in nursing. A search was conducted using CINAHL, MEDLINE, Ebscohost, and NCSBN. The key words searched were professional boundaries, boundary violation, boundary crossings, nurse, home health nurses, and home nursing. The search returned over 40 publications related specifically to boundary violations and nursing although only four of them are published research studies and one as a dissertation. Seven c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The importance of professional boundaries is well established in nursing, and is part of the standard of care for a therapeutic relationship . Nurses commit “boundary crossings” when doing tasks that are brief excursions intended to benefit the client . However, HC aides hold a different societal position from nurses and historically in the USA have been seen more as informal care providers than professionals .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of professional boundaries is well established in nursing, and is part of the standard of care for a therapeutic relationship . Nurses commit “boundary crossings” when doing tasks that are brief excursions intended to benefit the client . However, HC aides hold a different societal position from nurses and historically in the USA have been seen more as informal care providers than professionals .…”
Section: Discussionmentioning
confidence: 99%
“…37 Our Phase 1 formative research showed that in-service trainings and client intake assessment are crucial intervention points in addressing aide health and safety concerns 10 The importance of professional boundaries is well established in nursing, and is part of the standard of care for a therapeutic relationship. [40][41][42] Nurses commit "boundary crossings" when doing tasks that are brief excursions intended to benefit the client. 41 However, HC aides hold a different societal position from nurses and historically in the USA have been seen more as informal care providers than professionals.…”
Section: Possible Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This continuum promotes an ideal of correct behaviour for professional practice (National Council of State Boards of Nursing 2014; Nursing and Midwifery Board of Australia 2010; Nursing & Midwifery Council 2015; Nursing Council of New Zealand 2012). Violations of boundaries such as excessive self-disclosure and acceptance of gifts are seen as transgressions within the relationship (Manfrin-Ledet et al 2015). The nurse is expected to be responsible and maintain professional boundaries as these “are the spaces between the nurse’s power and the patient’s vulnerability” (National Council of State Boards of Nursing 2014, p. 4).…”
Section: The Nurse As Multi-beingmentioning
confidence: 99%
“…The scope of this problem has not been investigated adequately (Swiggart, Starr, Finlayson, & Spickard, ), especially in nursing (Manfrin‐Ledet, Porche, & Eymard, ), a profession in which the risk of sexual misconduct is high because nurses often spend long hours with their patients and the care that they provide often involves close proximity to patients (Bachmann et al, ; Griffith & Tengnah, ). This prolonged closeness may make it more difficult for nurses than other health care professionals to maintain clear roles and boundaries (Bachmann et al, ).…”
Section: Introductionmentioning
confidence: 99%